Being inclusive boosts impact of diversity practices on employee engagement - Jerónimo, Helena (2022)
Purpose – This study aims to analyse the relationship between diversity practices and employee engagement in the specific context of a telecommunications company. Design/methodology/approach – Using simple and multiple linear regressions, the authors test the mediating effect of the perception of inclusion and the moderating role of inclusive leadership, as well as whether this style of leadership promotes the perception of inclusion among employees. Findings – The results are based on a sample of 238 responses and show that a positive correlation exists between the perception of diversity practices and engagement which is mediated by the perception of inclusion. However, inclusive leadership fails to moderate this relationship, although it does positively influence employees’ perception of inclusion. Practical implications – The study emphasises: the importance of employees’ perceptions of diversity and inclusion as a strategic priority of their organisations and the importance of its embeddedness in the organisational culture and daily practices and the role of inclusive leaders in shaping employees’ perceptions, as this leadership may have significant implications for their engagement and performance. Originality/value – This research offers a better understanding of what contributes to an inclusive workplace and the role of inclusive leaders in building up employees’ perception of inclusion that, thus, enhances their engagement. .